Krytyka „Wiadomości” - Lutomierski, Marcin (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
Rafał Moczkodan’s monograph entitled ‘Omawiacze, laurkodawcy’, publicyści i krytycy. Krytyka literacka na łamach ‘Wiadomości’ w latach 1946–1956 is the first attempt to tackle the problem suggested by the title. The reviewed work is well documented: all opinions and theses which are presented find their justification in the rich bibliography (including sources which are not only literary criticism texts), which the author is well versed on. Furthermore, the monograph has been written in a precise and interesting way, making the book an incentive to continue research on criticism and literary journalism in the area of ‘Wiadomości’.
Criticism of ‘Wiadomości’
Keywords: pismo; krytyka; źródła; publicystyka; writing; criticism; bibliography; journalism